Everyday life in nursing work under the Michel de Certeau's perspective - Hosana Ferreira Rates; Ricardo Bezerra Cavalcante; Regina Consolação dos Santos; Marilia Alves
ABSTRACT Objective: to reflect on the everyday life in nursing work based on Michel de Certeau's theorization. Results: everyday life in nursing work is permeated by tactics of subjects who practice the place. Their movements escape standards, protocols and rules, re-signifying the cultural system defined beforehand. There is a practice proper to professionals who (re)invent the care based on their intentions and pressures. Patients/users also move, create their own itinerary and, similarly to professionals, use strategies to achieve specific results in the therapeutic process. Conclusion: to think on the everyday life in nursing work as an object of research requires to consider the care (re)invention in every act in health care. We need to dive into the invisible dimension of the uncontrollable tactics of subjects that re-signify the social system.